A brief study of the farmer's University on-the-air of the Bureau of Agricultural Extension. - Barbasa, Irene B.; Gustilo, Irene B.; Vargas, Maritess V. (1979.)
no abstract
Research Paper (Undergraduate, Senior Colloquium) Division of Social Sciences, University of the Philippines College Iloilo. 1979.
Keywords: Bureau of Agricultural Extension